2015
DOI: 10.1155/2015/371625
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Anthraquinonic Dyes from Textile Effluent Using Horseradish Peroxidase: Optimization and Kinetic Study

Abstract: Two anthraquinonic dyes, C.I. Acid Blue 225 and C.I. Acid Violet 109, were used as models to explore the feasibility of using the horseradish peroxidase enzyme (HRP) in the practical decolorization of anthraquinonic dyes in wastewater. The influence of process parameters such as enzyme concentration, hydrogen peroxide concentration, temperature, dye concentration, and pH was examined. The pH and temperature activity profiles were similar for decolorization of both dyes. Under the optimal conditions, 94.7% of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 37 publications
1
42
0
1
Order By: Relevance
“…The optimum pH for decoloring AV 109 and RB 19 was 4.5 and 5.0, respectively; the difference on the optimum pH might result from the structural feature of anthraquinone dyes; RB 19 with two SO 3 – groups was more sensitive to solution pH than AV 109 bearing one SO 3 – group. It has been reported that the free HRP showed the highest decolorization of AV 109 at pH 4.0 ; this pH shift toward alkaline zone could be ascribed to the interactions between the dyes and the support. Some reports have evidenced that support with charged surface such as Cu(II) ion incorporated membranes may alter the effect of pH on catalytic profile of enzymes .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The optimum pH for decoloring AV 109 and RB 19 was 4.5 and 5.0, respectively; the difference on the optimum pH might result from the structural feature of anthraquinone dyes; RB 19 with two SO 3 – groups was more sensitive to solution pH than AV 109 bearing one SO 3 – group. It has been reported that the free HRP showed the highest decolorization of AV 109 at pH 4.0 ; this pH shift toward alkaline zone could be ascribed to the interactions between the dyes and the support. Some reports have evidenced that support with charged surface such as Cu(II) ion incorporated membranes may alter the effect of pH on catalytic profile of enzymes .…”
Section: Resultsmentioning
confidence: 92%
“…The positively‐charged ZnO nanowires exhibited attracting force toward anthraquinone dye molecules and promoted the decolorization reaction. If the decolorization of AV 109 was catalyzed by free HRP, there would be a serious inhibitory activity from solution pH; as the pH was outside the range of 3.0–7.0, almost no decolorization efficiency could be observed . Obviously, the immobilized HRP on the nanocomposite support exhibited good activity in a more wide range of pH than did the free one, which is very important for the application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The residual amount of dye was followed using UV-Vis spectrophotometer (UV Shimadzu 1700, Shimadzu Corporation, Kyoto, Japan) at maximum wavelength for tested dye (λ max 590 nm AV 109). Decolorization was calculated using following mathematical expression [6]:…”
Section: Decolorization Of Anthraquinone Dye Av 109mentioning
confidence: 99%
“…Use of horseradish peroxidase (E.C. 1.11.1.7) appeared to be very efficient as well as eco-friendly method for decolorization of wastewaters [4,[6][7][8]. Disadvantages of free enzyme application such as: instability, denaturation, impossibility of recovery and purification, contamination or proteolysis can be overcome by using their immobilized counterparts [9,10].…”
Section: Introductionmentioning
confidence: 99%